Clinical Events After Discontinuation of β-Blockers in Patients Without Heart Failure Optimally Treated After Acute Myocardial Infarction: A Cohort Study on the French Healthcare Databases. Issue 4 (April 2018) - Neumann, Anke; Maura, Géric; Weill, Alain; Alla, François; Danchin, Nicolas
Abstract : Background: β-blockers have been among the first medications shown to improve outcomes after acute myocardial infarction (AMI). With the advent of reperfusion therapy and other secondary-prevention medications, their role has become uncertain, and large-scale experience after AMI in the contemporary era is lacking. In particular, the effect of stopping β-blockers in patients initially treated after AMI is unknown. Methods and Results: Using the French healthcare databases, 73 450 patients (<80 years of age), admitted for AMI in 2007 to 2012, without acute coronary syndrome (ACS) in the previous 2 years and no evidence of heart failure, having received optimal treatment with myocardial revascularization and all recommended medications in the 4 months after index admission, and not having discontinued β-blockers before 1 year, were followed for 3.8 years on average. β-Blocker discontinuation was defined as 4 consecutive months without exposure. If β-blocker treatment was resumed later on, follow-up was stopped. Both the risk of the composite outcome of death or admission for ACS and the risk of all-cause mortality were assessed in relation with β-blocker discontinuation during follow-up. Adjusted hazard ratios were estimated using marginal structural models accounting for time-varying confounders affected by previous exposure. A similar analysis was performed with statins. Of 204 592 patient-years, 12 002 (5.9%) corresponded to discontinued β-blocker treatment. For β-blocker discontinuation, the adjusted hazard ratio for death or ACS was 1.17 (95% confidence interval, 1.01–1.35); for all-cause death, the adjusted hazard ratio was 1.13 (95% confidence interval, 0.94–1.36). In contrast, for statin discontinuation, the adjusted hazard ratios for death or ACS and for all-cause death were 2.31 (95% confidence interval, 2.01–2.65) and 2.57 (95% confidence interval, 2.19–3.02), respectively. Conclusions: In routine care of patients without heart failure, revascularized and optimally treated after AMI, discontinuation of β-blockers beyond 1 year after AMI was associated with an increased risk of death or readmission for ACS, while statistical significance was not reached for the association with all-cause mortality. A contemporary randomized clinical trial is needed to precise the role of β-blockers in the long-term treatment after AMI. Abstract : Supplemental Digital Content is available in the text.